Development and Validation of 2D Difference Intensity Analysis for Chemical Library Screening by Protein‐Detected NMR Spectroscopy. (25th January 2018) - Egner, John M.; Jensen, Davin R.; Olp, Michael D.; Kennedy, Nolan W.; Volkman, Brian F.; Peterson, Francis C.; Smith, Brian C.; Hill, R. Blake
Abstract: An academic chemical screening approach was developed by using 2D protein‐detected NMR, and a 352‐chemical fragment library was screened against three different protein targets. The approach was optimized against two protein targets with known ligands: CXCL12 and BRD4. Principal component analysis reliably identified compounds that induced nonspecific NMR crosspeak broadening but did not unambiguously identify ligands with specific affinity (hits). For improved hit detection, a novel scoring metric—difference intensity analysis (DIA)—was devised that sums all positive and negative intensities from 2D difference spectra. Applying DIA quickly discriminated potential ligands from compounds inducing nonspecific NMR crosspeak broadening and other nonspecific effects. Subsequent NMR titrations validated chemotypes important for binding to CXCL12 and BRD4. A novel target, mitochondrial fission protein Fis1, was screened, and six hits were identified by using DIA. Screening these diverse protein targets identified quinones and catechols that induced nonspecific NMR crosspeak broadening, hampering NMR analyses, but are currently not computationally identified as pan‐assay interference compounds. The results established a streamlined screening workflow that can easily be scaled and adapted as part of a larger screening pipeline to identify fragment hits and assess relative binding affinities in the range of 0.3–1.6 mm . DIA could prove useful in library screening and other applications in which NMR chemical shift perturbations are measured. Abstract : Can you tell the difference? Difference intensity analysis of fragment‐based screening by NMR 2D difference spectra enabled us to quickly discriminate potential chemical fragment hits from non‐hits, compounds inducing nonspecific NMR crosspeak broadening, and other nonspecific effects. This quantitative NMR spectral analysis method could assist in library screening and other applications in which NMR chemical‐shift perturbations are measured.